2019
DOI: 10.1029/2019gl083372
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Rising Tone Whistler Mode Waves Inside the Earth's Plasmasphere, Plasmaspheric Plumes, and Plasmatrough

Abstract: Whistler mode waves, particularly rising tone emissions, are important for nonlinear interactions with energetic electrons in the Earth's magnetosphere. In this letter, we evaluate the characteristics of rising tone whistler mode waves in three distinct regions: (1) inside the plasmasphere, (2) plasmapheric plumes, and (3) plasmatrough (outside the plasmapause). Our statistical results indicate that the occurrence rate of rising tone emissions tends to increase with increasing geomagnetic activity and is highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
(116 reference statements)
1
10
0
Order By: Relevance
“…A coherent relatively large amplitude LF (and HF) hiss were detected in plasma plumes (L > 7). Hiss inside plumes have been reported previously (Shi et al, ; Summers et al, ; Teng et al, ; Tsurutani et al, ). We argue that because plumes are relatively small regions of space, the Thorne et al () mechanism of circulation of local plasmaspheric hiss with multiple passages through the generation region will not be applicable.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A coherent relatively large amplitude LF (and HF) hiss were detected in plasma plumes (L > 7). Hiss inside plumes have been reported previously (Shi et al, ; Summers et al, ; Teng et al, ; Tsurutani et al, ). We argue that because plumes are relatively small regions of space, the Thorne et al () mechanism of circulation of local plasmaspheric hiss with multiple passages through the generation region will not be applicable.…”
Section: Discussionsupporting
confidence: 72%
“…Circulation models cannot be applied for such small regions of space. Recent works on hiss within plumes (Hartley et al, 2019;Li et al, 2019;Nakamura et al, 2018;Shi et al, 2019;Teng et al, 2019;Zhang et al, 2018), although not the main focus of this paper, will be commented on in sections 4 and 5 of this paper in this light.…”
Section: Introductionmentioning
confidence: 99%
“…Whistler mode waves are often observed in plasmaspheric plumes (Chan & Holzer, 1976; Hayakawa et al, 1986; Li et al, 2019; Shi et al, 2019; Su et al, 2018; Tsurutani et al, 2015), which are composed of plasma being drained from the reservoir of plasmaspheric plasma and extending into the more tenuous outer magnetosphere (Chen & Wolf, 1972; Elphic et al, 1996; Goldstein et al, 2004; Grebowsky, 1970; Weiss et al, 1997). Whistler mode waves in plumes are found to exhibit broadband emissions or discrete rising tones (Nakamura et al, 2018; Shi et al, 2019; Su et al, 2018; Teng et al, 2019) and typically have stronger wave amplitudes, up to 1.5 nT (Su et al, 2018) than typical plasmaspheric hiss (Shi et al, 2019). Due to larger wave amplitudes and higher ratio of plasma to electron cyclotron frequency in plumes (compared to plasmasphere or plasmasheet), pitch angle scattering loss driven by whistler mode waves in plumes could be stronger than plasmaspheric hiss, particularly at lower energy (W. Li et al, 2019), suggesting their potential importance in energetic electron loss process (e.g., Summers et al, 2008; W. Zhang, Fu, et al, 2018).…”
Section: Local Energy and Pitch Angle Scatteringmentioning
confidence: 99%
“…Generally, Chorus wave is considered to be excited through the cyclotron resonance with anisotropic energetic electrons near the magnetic equator outside the plasmasphere (H. Li et al., 2016a; W. Li et al., 2009b, Tang et al., 2014; Tang & Summers, 2019, Zhang et al., 2020; Summers & Tang, 2021). They are primarily distributed outside the plasmasphere on the dawn side (Teng et al., 2018a; Teng et al., 2019). Previous research has suggested that strong chorus in the frequency range 200 < f < 2,000 Hz can extend to higher magnetic latitudes under active conditions (Meredith et al., 2021).…”
Section: Introductionmentioning
confidence: 99%